Artemis Fowl. The opal deception - Colfer, Eoin (Colfer, Eoin. Artemis Fowl, 2018)
Artemis Fowl must again prevent the human and fairy worlds from colliding. He is in Berlin preparing to steal a painting from a German bank. His evil pixie rival, Opal Koboi, is out of her coma and clones herself to be a human. She first lures Captain Holly Short and Commander Root into a trap then works to outsmart and destroy Artemis.